On the exact solutions of high order wave equations of KdV type (I) - Bulut, Hasan; Pandir, Yusuf; Baskonus, Haci Mehmet (Amer Inst Physics, 2014)
In this paper, by means of a proper transformation and symbolic computation, we study high order wave equations of KdV type (I). We obtained classification of exact solutions that contain soliton, rational, trigonometric and elliptic function solutions by using the extended trial equation method. As a result, the motivation of this paper is to utilize the extended trial equation method to explore new solutions of high order wave equation of KdV type (I). This method is confirmed by applying it to this kind of selected nonlinear equations.
10th International Conference on Mathematical Problems in Engineering, Aerospace and Sciences (ICNPAA) -- JUL 15-18, 2014 -- Narvik Univ Coll, Narvik, NORWAY
Keywords: The extended trial equation method; High order wave equations of KdV type (I); The rational function solution; The exponential function solution; Elliptic function solutions